The Adventure Time encyclopaedia : inhabitants, lore, spells, and ancient crypt warnings of the land of Ooo circa 19.56 b.g.e. - 501 a.g.e. - Olson, Martin (Abrams, 2013)
Written and compiled by the Lord of Evil himself, The Adventure Time Encyclopaedia matches the playful, subversive tone of the cartoon series, detailing everything anyone will ever need to know about the postapocalyptic land of Ooo and its inhabitants-- secret lore and spells, fun places you should visit and places where you will probably die, whom to marry and whom not to marry, how to make friends and how to destroy your enemies-- plus hand-written marginalia by Finn, Jake, and Marceline. An indispensable companion to the show, this side-splittingly funny love letter to Adventure Time is sure to appeal to fans of all ages. Heck yeah!